Chronic Energy Deficiency in Women from Muna District: Association with Body Image and Knowledge - Astuti, Cece; Majid, Ruslan; Prasetya, Fikki (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
One of the nutritional problems in pregnant women is Chronic Energy Deficiency (CED). Chronic Energy Deficiency is a condition of pregnant women who suffer from a long-lasting (chronic) lack of food with various health problems in pregnant women. The purpose of this study was to determine the factors associated with the incidence of Chronic Energy Deficiency in pregnant women in Muna Regency. The focus of this research is on pregnant women in the working area of the Maabodo Health Center. The type of research used in this study is a quantitative research type with an analytical survey design with a cross-sectional approach. This research was conducted in the working area of the Maabodo Health Center, Muna Regency and this study was conducted in September 2020. The population in this study were all pregnant women in the working area of the Maabodo Health Center as many as 57 people using a total sampling technique. Based on the results of the chi-square test, there is a relationship between knowledge and the incidence of CED (p-value = 0.026) and there is a relationship between body image and the incidence of CED (p-value = 0.009). However, there is no relationship between parity and the incidence of CED (p-value = 0.110). This study found that the mother's knowledge factor and mother's body image played an important role in preventing the occurrence of Chronic Energy Deficiency (CED) in pregnant women in Indonesia.